Team Jarts Rocket Design - Folz, Alex; Foster, Brett; Logisz, Eric; Schulz, Cameron (Proceedings of the Wisconsin Space Conference, 2012)
The objective of the 2012 Wisconsin Space Grand Consortium collegiate rocket competition was to construct a rocket capable of live video feed through the thrust phase while flying to an exact altitude of 3,000 feet. The airframe of the rocket was designed utilizing a simplistic, low weight design to provide a properly balanced rocket. The main chute was designed for two separate scenarios of deployment; the first scenario involves a remote controlled manual deployment, and the other is activated by an automatic elevation trigger, which will serve as a failsafe to ensure the rocket makes a safe landing. A numerical simulation, developed in MATLAB, was used to predict the performance of the rocket. The maximum predicted acceleration calculated is 506 ð’‡ð’•/ð’”ðŸ, and the maximum predicted altitude calculated is 3480.6 ð’‡ð’†ð’†ð’•. Further analysis of the rocket design and discrepancies are attached below.Â